Emerging Alzheimer’s disease therapeutics: promising insights from lipid metabolism and microglia-focused interventions - Tobeh, Nour S.; Bruce, Kimberley D. (Frontiers in Aging Neuroscience, 2023)
More than 55 million people suffer from dementia, with this number projected to double every 20 years. In the United States, 1 in 3 aged individuals dies from Alzheimer's Disease (AD) or another type of dementia and AD kills more individuals than breast cancer and prostate cancer combined. AD is a complex and multifactorial disease involving amyloid plaque and neurofibrillary tangle formation, glial cell dysfunction, and lipid droplet accumulation (among other pathologies), ultimately leading to neurodegeneration and neuronal death. Unfortunately, the current FDA-approved therapeutics do not reverse nor halt AD. While recently approved amyloid-targeting antibodies can slow AD progression to improve outcomes for some patients, they are associated with adverse side effects, may have a narrow therapeutic window, and are expensive. In this review, we evaluate current and emerging AD therapeutics in preclinical and clinical development and provide insight into emerging strategies that target brain lipid metabolism and microglial function -an approach that may synergistically target multiple mechanisms that drive AD neuropathogenesis. Overall, we evaluate whether these disease-modifying emerging therapeutics hold promise as interventions that may be able to reverse or halt AD progression.